do this question please i requested u
Attachments:
![](https://hi-static.z-dn.net/files/d10/06d1a36ec696d0cc6f39754e5e149f83.jpg)
Answers
Answered by
1
Soln:-
=(2a-3b)^2.
=(2a)^2- 2×2a×3b + (3b)^2
=4a^2 -12ab +9b^2
=4×8^2 - 12×8×4 +9×4^2
=16
=(2a-3b)^2.
=(2a)^2- 2×2a×3b + (3b)^2
=4a^2 -12ab +9b^2
=4×8^2 - 12×8×4 +9×4^2
=16
Answered by
0
Answer:
-368 is your answer
Step-by-step explanation:
(2a-3b)²
= 4a²-2(2a)(3b)+(3b)²
= 4a²-(4a)(6b)+9b²
= 4a²-24ab+9b²
Now putting the values of a=8 and b=4:
4a²-24ab+9b²
4(8)²-24(8)(4)+9(4)²
256-768+144
400-768
-368 is your answer
shubhamkumar20061001:
u did wrong
Similar questions
Biology,
8 months ago
Math,
8 months ago
Social Sciences,
8 months ago
Hindi,
1 year ago
History,
1 year ago
Math,
1 year ago
Math,
1 year ago
Computer Science,
1 year ago